Unconjugated Side‐Chain Engineering Enables Small Molecular Acceptors for Highly Efficient Non‐Fullerene Organic Solar Cells: Insights into the Fine‐Tuning of Acceptor Properties and Micromorphology. (6th May 2019) - Liu, Tao; Gao, Wei; Wang, Yilin; Yang, Tao; Ma, Ruijie; Zhang, Guangye; Zhong, Cheng; Ma, Wei; Yan, He; Yang, Chuluo
Abstract: 2D conjugated side‐chain engineering is an effective strategy that is widely utilized to construct benzodithiophene‐based polymers. Herein, an unconjugated side‐chain strategy to design fused‐benzodithiophene‐based non‐fullerene small molecule acceptors (SMAs) via vertical aromatic side‐chain engineering on the ladder‐type core is employed. Three SMAs named BTTIC‐Th, BTTIC‐TT, and BTTIC‐Ph with thiophene, thieno[3, 2‐ b ]thiophene, and benzene, respectively, as side chains, are designed and synthesized. Three SMAs exhibit similar absorption ranges but different lowest unoccupied molecular orbital (LUMO) energy levels due to the different strength of the δ‐inductive effect between vertical aromatic side chains and their electron‐rich core. Organic solar cells based on PBDB‐T:BTTIC‐TT achieve a power conversion efficiency (PCE) of 13.44%, which is higher than the PCE of devices based on PBDB‐T:BTTIC‐Th (12.91%) and PBDB‐T:BTTIC‐Ph (9.14%). The difference in device performance is investigated by electrical and morphological characterizations. A large domain size and different types of π–π stacking are found in the bulk heterojunction layer of PBDB‐T:BTTIC‐Ph blend film, which are detrimental to exciton dissociation and charge transport. Overall, it is demonstrated that when designing unconjugated side chains, thieno[3, 2‐ b ]thiophene is superior to thiophene and benzene through its dual roles of promoting the LUMO energy level and optimizing the morphology. These results shed light on the side‐chain engineering of high‐performance non‐fullerene SMAs. Abstract : Unconjugated side‐chain engineering is performed on non‐fullerene small molecule acceptors based on a fused‐benzodithiophene core. Thieno[3, 2‐ b ]thiophene is superior to thiophene and benzene owing to its dual roles of promoting the molecular energy level (δ‐inductive effect) and optimizing the morphology. Thus, organic solar cells based on PBDB‐T:BTTIC‐TT achieve the highest power conversion efficiency of 13.44% among three devices.